Editorial Note for the Second Issue of the Journal of Green Technology and Environment in 2023 - Birinci, Emre (Zenodo, 2023)
Technology is the application of academic knowledge to practical needs. Green technologies help to reduce the impact of the application of technology to functional requirements on the environment and create sustainable development pathways. One of the most important causes of environmental pollution is waste disposal. With green technology, waste generation can be transformed and greened in a way that does not harm the planet. Possible areas where new technologies are expected to be developed in this context include green energy, organic agriculture, environmentally friendly textiles, green building construction, and the production of related products and materials to support green business. This way, future generations can benefit from green technologies without harming the planet. Journal of GreenTech focuses on the development and dissemination of green technologies. For this reason, the Editorial Board of the Journal of GreenTech has reached a consensus that multidisciplinary academic studies in the fields of green technology and environment should be evaluated in the Journal of GreenTech. The second issue of the Journal of GreenTech for 2023 contains a total of six research articles. The first article was written by Ayata. In this study, researchers heat-treated ten different tropical woods at 200°C and examined the changes in their physical properties. Narlıoğlu wrote the second article. In the related article, the author investigated the effect of chemical modification on FTIR crystallinity indexes in oak wood. The chemical modification method basically extends the service life of the wood material and improves some physical, mechanical, and biological properties. This will ensure that wood is preferred over plastic materials, which are used extensively today and take millions of years to recycle. In the Journal of GreenTech, the study conducted by Demirel and Sivrikaya was listed in third place. In this study, various evaluations and mapping were made in order to determine the temporal and spatial changes in land use/land cover between 1999-2011 in Inebolu Forestry Enterprise located in the Western Black Sea Region of Turkey and to reveal the reasons for these changes using Geographic Information Systems. The fourth article was conducted by Peker, Ayata and Çamlıbel. In this article, the researchers investigated the changes in surface roughness parameters and shore D hardness value of okan (Cylicodiscus gabu-nensis [Taub.] Harms) wood, which is used in many countries in areas such as park/garden furniture, carving and turning. The fifth and last article of the issue was conducted by Bakırcı, Polat and Özdemir. The need for renewable and clean energy is highlighted in detail in this successful research paper. In order to increase the efficiency of wind turbines, HAD analysis of the NACA 4412 airfoil, which can be used in small-scale wind turbine design, was performed. It is thought that this issue, which includes studies carried out by valuable scientists, will attract the attention of researchers and readers in different disciplines.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land; 7. Clean energy; 12. Responsible consumption